CSR Disclosure in State Owned Enterprises in Indonesia: Does Public Share Ownership could Effect? - Merawati, Luh Komang; Yuliastuti, Ida Ayu Nyoman; Pradnyana, I Made Adhi (Ratio : Reviu Akuntansi Kontemporer Indonesia, 2022)
Social responsibility is one of the company’s programs in the form of accountability to overcome social problems and environmental damage done by the company itself. This form of accountability can be realized by disclosing CSR. This study aims to test and obtain empirical evidence of the influence of profitability, company size, leverage, board of commissioner and public share ownership against the disclosure of CSR in state-owned enterprises. Sample used is 20 companies of Â state-owned enterprises in three years of observation. The data analysis technique used is multiple linear regression. The results revealed that the profitability and size of the board of commissioners had a positive effect on CSR disclosure, while the size of the company, leverage, and public share ownership had no effect on CSR disclosure. Â Keywords: corporate social responsibility, leverage, size, profitability, public share ownership